Addition flame-retardant behaviors of expandable graphite and [bis(2-hydroxyethyl)amino]-methyl-phosphonic acid dimethyl ester in rigid polyurethane foams. (December 2015) - Xi, Wang; Qian, Lijun; Chen, Yajun; Wang, Jingyu; Liu, Xinxin
Abstract: The flame-retardant rigid polyurethane foams (RPUFs) with [bis(2-hydroxyethyl)amino]-methyl-phosphonic acid dimethyl ester (BH)/expandable graphite (EG) were prepared via box-foaming in our laboratory. The flame retardancy of RPUFs with BH and EG was characterized using the limiting oxygen index (LOI), cone calorimeter test. The results show that BH/EG system obviously increased the LOI value, decreased the heat release rate and mass loss rate, and enhanced the char yields of RPUFs. The results reveal that the addition flame-retardant effects from BH and EG. The flame-retardant mechanism of RPUFs was also detected using scan electronic microscopic and pyrolysis-gas chromatography/mass spectroscopy. According to the test results, BH promoted forming the firm phosphorus-containing char layer, which adhered the loose and worm-like expanded graphite in condense phase. Then, the compacter and thicker char layer was obtained. It will exert well obstructing property to fire in condensed phase. Moreover, BH also will generate dimethyl methylphosphonate (DMMP) gas and then be pyrolyzed to PO and PO2 free radicals in gaseous phase during combustion, which can quench the flammable free radicals from the matrix and terminate the free radical chain reaction of combustion. After the combination of the bi-phase flame-retardant effects, BH/EG flame-retardant system brought addition flame-retardant effects, and thus providing the better flame retardancy to matrix than one of them does. Moreover, the results of compressive strength, thermal conductivity and apparent density reveal that BH/EG/RPUF can meet the demand for the application in reality.